2021
DOI: 10.1523/jneurosci.2450-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Shared Dorsal Periaqueductal Gray Activation Patterns during Exposure to Innate and Conditioned Threats

Abstract: The brainstem dorsal periaqueductal gray (dPAG) has been widely recognized as being a vital node orchestrating the responses to innate threats. Intriguingly, recent evidence also shows that the dPAG mediates defensive responses to fear conditioned contexts. However, it is unknown whether the dPAG displays independent or shared patterns of activation during exposure to innate and conditioned threats. It is also unclear how dPAG ensembles encode and predict diverse defensive behaviors. To address this question, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…In the present study, using the Poisson GLM analysis estimating only the influence of the behaviours to predict the neuronal activity, we found an increase in cell firing during freezing (22% of the cells), risk assessment (49% of the cells), and exploratory behaviour (27% of the cells). Similar results were obtained in previous studies investigating mice during predatory exposure to a rat and reported dorsal PAG cells activated during various defensive behaviour, such as escape, freezing, and risk assessment (Deng et al, 2016; Masferrer et al, 2020; Reis et al, 2021). However, when the GLM model also controls for the stimulus conditions, the effect that the model found for each specific behaviour is far less pronounced (% of cells with increased firing during freezing [0%]; risk assessment [32%]; exploration [22%]).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the present study, using the Poisson GLM analysis estimating only the influence of the behaviours to predict the neuronal activity, we found an increase in cell firing during freezing (22% of the cells), risk assessment (49% of the cells), and exploratory behaviour (27% of the cells). Similar results were obtained in previous studies investigating mice during predatory exposure to a rat and reported dorsal PAG cells activated during various defensive behaviour, such as escape, freezing, and risk assessment (Deng et al, 2016; Masferrer et al, 2020; Reis et al, 2021). However, when the GLM model also controls for the stimulus conditions, the effect that the model found for each specific behaviour is far less pronounced (% of cells with increased firing during freezing [0%]; risk assessment [32%]; exploration [22%]).…”
Section: Discussionsupporting
confidence: 90%
“…During cat exposure (stimulus condition 3), the animals alternated between freezing and risk assessment, and most of the time stayed away from the cat. Thus, while we succeeded in our intention of exposing the rats to a very strong threat stimulus, unlike the more active interaction between mice and rats seen in the predatory interaction of the previous studies (Deng et al, 2016;Masferrer et al, 2020;Reis et al, 2021), our experimental approach rendered it difficult to differentiate cell populations responding to approaching or fleeing away from the predator. As the cat was removed from the stimulus box, the rat was kept in the experimental apparatus during the post-cat condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations